The Effect of Forgiveness and Spouse Social Support on Marital Satisfaction from the Perspective of Islamic Ethics - Zahrotun Nihayah; Sururin Sururin; Choirunnisa Choirunnisa; Dinnisa Haura Zhafira Hidayat; Syahirul Alim; Mohammad Fayruz (Islamic Guidance and Counseling Journal, 2023)
This study aims to examine the effects of forgiveness and spouse social support on marital satisfaction in working wives from the perspective of Islamic ethics. This quantitative study involved 225 participants from Indonesia and employed purposive sampling. Data were collected using a questionnaire with a Likert scale model and were analyzed using multiple regression analysis techniques with the aid of the SPSS 22 program. The findings show that 1) forgiveness and spouse social support variables have a simultaneous effect on marital satisfaction variables. The variables of forgiveness and spouse social support have a combined influence of 63.8% on the marital satisfaction variable, with the remaining 35.9% influenced by other unexamined variables; 2) The forgiveness variable has a partial effect on the marital satisfaction variable; and 3) The spouse social support variable has a partial effect on the marital satisfaction variable. Ethical entities such as forgiveness and spouse social support, in fact, have a significant influence in preventing larger conflicts that threaten the level of satisfaction and happiness in marriage. Happiness in general is seen as cognitive, conative, and accidental according to Islamic ethical theory. The harmonization of these three elements is crucial in Islamic ethical principles and, even further, becomes an important factor in achieving happiness. The implication of this research is that factors such as forgiveness and spouse social support play a significant role in marital satisfaction among working wives, particularly within the framework of Islamic ethics.